Investigation of the possible origins of sulfur in 19th century salted paper photographs by x‐ray fluorescence spectroscopy. (17th February 2016) - Sessa, Clarimma; Barro, Lisa; Centeno, Silvia A.; Bagán, Héctor; Carò, Federico; García, José Francisco
Abstract : An X‐ray fluorescence method to determine whether sulfur is present in 19th century photographs due to intentional toning or to environmental deterioration is proposed. In the 19th century salted paper print photographic process, AgCl formed on the surface of a sheet of paper was exposed to sunlight in contact with a negative, leading to the printing out of a Ag image that was fixed by immersing it in a sodium thiosulfate solution or hypo . The improper execution of the fixing in these photographs may result in the presence of sulfur, mostly manifested in image fading, irregular staining, and discoloration. Also, 19th century artists produced salted paper prints with a variety of image tonalities, for example, by using an artificially aged thiosulfate bath. The presence of sulfur in photographs may also be due to sulfur‐containing environmental pollutants. Therefore, knowledge about the location and amounts of sulfur is important to understand the artistic technique and/or the deterioration processes. In this study, the amounts of sulfur and the silver to sulfur signal ratios were determined for a salted paper print made in the laboratory following a 19th century procedure and for two artistic salted paper photographs using X‐ray fluorescence and standards prepared with different amounts of retained hypo and quantified by inductively coupled plasma atomic emission spectroscopy. The amounts of sulfur and the normalized silver to sulfur ratios for the artistic photographs were evaluated based on the results obtained in the samples prepared in the laboratory and in the context of the 19th century practices. Copyright © 2016 John Wiley & Sons, Ltd.